Asphalt concrete anti-stripping durable modifier and preparation method thereof

By using single-layer structure calcium-aluminum hydroxide, nanotitanium dioxide and phosphate coupling agent with a large specific surface area, the problem that existing anti-flaking agents are difficult to maintain the combination of asphalt concrete and aggregates is solved, and the anti-flaking and durability of asphalt concrete is significantly improved.

CN119898980AInactive Publication Date: 2025-04-29NORTHWEST ENGINEERING CORPORATION LIMITED
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510377207.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anti-flaking agents are difficult to effectively maintain the close bond between asphalt concrete and aggregate, resulting in frequent peeling problems, affecting durability and overall performance.

Method used

Calcium aluminum hydroxide with a single-layer structure with a larger specific surface area is used as the anti-flaking agent, and calcined at different temperatures through kaolin, quicklime and other materials, the double-layer structure is transformed into a single-layer structure, and the specific surface area is increased. Nanotitanium dioxide and phosphate coupling agent are added simultaneously to improve performance.

Benefits of technology

It significantly improves the anti-flaking and durability of asphalt concrete, enhances its ability to resist water damage, high-temperature flow, and low-temperature cracking, and improves the overall physical performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898980A_ABST
    Figure CN119898980A_ABST
Patent Text Reader

Abstract

The invention discloses an asphalt concrete anti-stripping durable modifier and a preparation method thereof, and the anti-stripping durable modifier comprises the following components in parts by weight: 90-105 parts of calcium aluminum hydroxide with a single-layer structure. The method comprises the following steps: calcining 80-90 parts by weight of kaolin with a first preset size at a first preset temperature for a first preset time, and then carrying out quenching treatment at a second preset temperature to obtain a first solid; adding the first solid and quick lime into water, stirring for a second preset time, and filtering to obtain a second solid, the quick lime being 65-75 parts by weight and the water being 90-100 parts by weight, the second solid comprising calcium-aluminum hydroxide of a double-layer structure; and calcining the second solid at a third preset temperature for a third preset time to obtain a third solid which comprises 90-105 parts by weight of calcium aluminum hydroxide with a single-layer structure. The calcium-aluminum hydroxide with a single-layer structure is large in specific surface area and has a larger action area with asphalt concrete and aggregate, so that the anti-stripping performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and in particular relates to an anti-stripping durable modifier for asphalt concrete and a preparation method thereof. Background Art

[0002] Asphalt concrete, as an important dam-building and anti-seepage material, plays a key role in the construction of water conservancy and hydropower projects.

[0003] Asphalt concrete has to withstand long-term immersion in water in the working environment, which will weaken the bonding force between asphalt concrete and aggregates, easily causing the asphalt concrete film to peel off from the aggregate surface, thereby reducing the anti-seepage performance. In order to improve the adhesion between aggregates and asphalt concrete, the existing technology usually adopts the method of adding anti-stripping agents. Anti-stripping agents can enhance the physical-chemical bonding between asphalt concrete and aggregates, and improve the adhesion between asphalt concrete and aggregates.

[0004] However, in a long-term working environment, existing anti-stripping agents are difficult to effectively maintain the close bonding between asphalt concrete and aggregates, resulting in frequent spalling problems, which affects the durability and overall performance of asphalt concrete. Summary of the invention

[0005] In order to solve the above problems, the present invention discloses an anti-stripping durable modifier for asphalt concrete and a preparation method thereof.

[0006] The invention discloses an anti-stripping durable modifier for asphalt concrete. The anti-stripping durable modifier comprises 90 to 105 parts of calcium aluminum hydroxide with a single-layer structure by weight.

[0007] Preferably, the anti-stripping durable modifier further comprises 1 to 5 parts by weight of nano titanium dioxide.

[0008] Preferably, the asphalt concrete anti-stripping durable modifier further comprises 1 to 2 parts by weight of a phosphate coupling agent.

[0009] The present invention also discloses a method for preparing an asphalt concrete anti-stripping durable modifier, comprising the following steps: calcining 80 to 90 parts by weight of kaolin of a first preset size at a first preset temperature for a first preset time, and then rapidly cooling at a second preset temperature to obtain a first solid; Adding the first solid and quicklime into water, stirring for a second preset time, and filtering to obtain a second solid, wherein the quicklime is 65 to 75 parts by weight, the water is 90 to 100 parts by weight, and the second solid comprises a double-layer structure of calcium aluminum hydroxide; The second solid is calcined at a third preset temperature for a third preset time to obtain a third solid, wherein the third solid comprises: 90 to 105 parts by weight of calcium aluminum hydroxide with a single-layer structure.

[0010] Preferably, after adding the first solid and quicklime into water, the method further comprises: 1 to 5 parts by weight of nano titanium dioxide are added to a mixture of the first solid, quicklime and water.

[0011] Preferably, after obtaining the third solid, the method further comprises: After the third solid is naturally cooled to room temperature, the third solid is mixed with 1 to 2 parts by weight of a phosphate coupling agent and crushed and ground to a powder fineness of a second preset size.

[0012] Preferably, the first preset temperature is 700°C to 900°C; the second preset temperature is 20°C to 40°C; and the third preset temperature is 300°C to 500°C.

[0013] Preferably, the first preset time is 3h~5h; the second preset time is 5h~7h; and the third preset time is 2h~4h.

[0014] Preferably, the first preset size is: the fineness satisfies that the pass rate of the 45µm square hole sieve is greater than 99%; the second preset size is: the fineness satisfies that the pass rate of the 45µm square hole sieve is greater than 90%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a single-layer calcium aluminum hydroxide with a large specific surface area as an anti-stripping agent. After being added to asphalt concrete, it has a larger effective area with the asphalt concrete and the aggregate interface, so the asphalt concrete added with the present invention has better anti-stripping performance; (2) The asphalt concrete anti-stripping and durable modifier of the present invention uses kaolin and quicklime as main raw materials and is calcined in sequence at different temperatures, thereby converting the double-layer structure of calcium aluminum hydroxide into a single-layer structure, achieving a significant increase in the specific surface area of ​​calcium aluminum hydroxide. The preparation method is not only simple to operate and easy to control, but also effectively improves the performance of the anti-stripping and durable modifier, providing asphalt concrete with excellent anti-stripping and durability performance; (3) The single-layer calcium aluminum hydroxide used in the present invention can reduce direct exposure to ultraviolet rays by physically shielding them, thereby reducing their damage and aging effects on asphalt concrete; (4) Furthermore, the single-layer calcium aluminum hydroxide used in the present invention can change the physical properties of asphalt concrete, such as viscoelasticity, creep deformation and elastic deformation, and improve the fatigue resistance of asphalt concrete. It can also improve the high-temperature stability, making it less likely to flow and deform under high temperature conditions, and improve the low-temperature crack resistance, preventing the asphalt concrete from cracking and damage under low temperature conditions. (5) The present invention can significantly improve the elastic modulus, yield stress and rheological properties of asphalt concrete and enhance its anti-deformation ability by adding nano-titanium dioxide with extremely small particle size and large specific surface area as powder filler. The nano-titanium dioxide of the present invention can also improve the adhesion between asphalt concrete and aggregate, reduce water damage, and enhance the anti-water damage performance of asphalt concrete; (6) The nano titanium dioxide of the present invention can improve the anti-aging performance of asphalt concrete, reduce the ductility loss rate of asphalt concrete under ultraviolet irradiation, reflect solar ultraviolet rays and increase heat dissipation, thereby reducing the surface temperature of asphalt concrete and improving the high-temperature stability of asphalt concrete; (7) The present invention contains micron-sized single-layer calcium aluminum hydroxide crystals, nano titanium dioxide and phosphate coupling agent modifiers, which can simultaneously improve the anti-stripping performance and durability (water stability, high temperature stability, low temperature stability, and anti-ultraviolet aging performance) of asphalt concrete; (8) The present invention mixes nano-titanium dioxide with a single-layer calcium aluminum hydroxide and calcines at low temperature, so that the nano-titanium dioxide can be attached to the single-layer calcium aluminum hydroxide, achieving a better dispersion effect and avoiding the agglomeration and failure of the nanoparticles; further, the reaction activity of the nano-titanium dioxide can be increased by calcining at low temperature, so that the nano-titanium dioxide calcined at low temperature has an improvement effect on the durability and water stability of asphalt concrete; (9) The present invention adds a phosphate coupling agent. On the one hand, its multiple polar groups can be adsorbed on the surface of the single-layer calcium aluminum hydroxide and aggregate (such as acidic stone) respectively, so as to achieve uniform dispersion of the single-layer calcium aluminum hydroxide and avoid its agglomeration problem; on the other hand, its non-polar groups can combine with asphalt concrete, thereby closely combining the aggregate and asphalt concrete. This mechanism of action can significantly improve the anti-stripping performance of the asphalt concrete mixture and reduce the erosion of water on the asphalt concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the XRD pattern of calcium aluminum hydroxide with a double-layer structure; Figure 2 This is the XRD pattern of calcium aluminum hydroxide with a single layer structure; Figure 3It is a diagram showing the mechanism of the transformation of calcium aluminum hydroxide from a double-layer structure to a single-layer structure and the attachment of nano-titanium dioxide to the single-layer structure of calcium aluminum hydroxide. DETAILED DESCRIPTION

[0017] In the following description, specific details such as specific system structures, technologies, etc. are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present invention.

[0018] The invention discloses an anti-stripping durable modifier for asphalt concrete, which comprises 90 to 105 parts by weight of calcium aluminum hydroxide with a single-layer structure.

[0019] The present invention adopts calcium aluminum hydroxide with a single-layer structure having a large specific surface area as an anti-stripping agent. After being added to asphalt concrete, it has a larger effective area with the asphalt concrete and the aggregate interface, so the present invention has better anti-stripping performance.

[0020] Preferably, the anti-stripping durable modifier also includes 1 to 5 parts of nano titanium dioxide by weight.

[0021] The present invention can significantly improve the elastic modulus, yield stress and rheological properties of asphalt concrete and enhance its anti-deformation ability by adding nano titanium dioxide with extremely small particle size and large specific surface area as powder filler; nano titanium dioxide can also improve the adhesion between asphalt concrete and aggregate, reduce water damage, and thus enhance the anti-water damage performance of asphalt concrete; Furthermore, the nano titanium dioxide of the present invention can improve the anti-aging performance of asphalt concrete, reduce the ductility loss rate of asphalt concrete under ultraviolet irradiation, and at the same time, the nano titanium dioxide can reflect solar ultraviolet rays and increase heat dissipation, thereby reducing the surface temperature of asphalt concrete and improving the high-temperature stability of asphalt concrete.

[0022] Preferably, the asphalt concrete anti-stripping durable modifier further comprises 1 to 2 parts of a phosphate coupling agent by weight.

[0023] The present invention adds a phosphate coupling agent. On the one hand, its multiple polar groups can be adsorbed on the surface of the single-layer calcium aluminum hydroxide and aggregate (such as acidic stone) respectively, so as to achieve uniform dispersion of the single-layer calcium aluminum hydroxide and avoid agglomeration problems; on the other hand, its non-polar groups can be combined with asphalt concrete, thereby closely combining the aggregate and asphalt concrete. This mechanism of action can significantly improve the anti-stripping performance of asphalt concrete and reduce the erosion of moisture on the asphalt concrete structure.

[0024] The present invention also discloses a method for preparing an asphalt concrete anti-stripping durable modifier, comprising the following steps: calcining 80 to 90 parts by weight of kaolin of a first preset size at a first preset temperature for a first preset time, and then rapidly cooling at a second preset temperature to obtain a first solid; Adding the first solid and quicklime into water, stirring for a second preset time, and filtering to obtain a second solid, wherein the quicklime is 65 to 75 parts by weight, and the water is 90 to 100 parts by weight, and the second solid includes calcium aluminum hydroxide with a double-layer structure; The second solid is calcined at a third preset temperature for a third preset time to obtain a third solid, wherein the third solid includes: 90 to 105 parts by weight of calcium aluminum hydroxide with a single-layer structure.

[0025] Preferably, the first preset temperature is 700°C to 900°C; the second preset temperature is 20°C to 40°C; and the third preset temperature is 300°C to 500°C.

[0026] The first preset time is 3h~5h; the second preset time is 5h~7h; the third preset time is 2h~4h.

[0027] The first preset size is: the fineness meets the pass rate of 45µm square hole sieve greater than 99%.

[0028] Preferably, after adding the first solid and quicklime into water, the method further comprises: 1 to 5 parts by weight of nano titanium dioxide are added to a mixture of the first solid, quicklime and water.

[0029] The invention mixes nano titanium dioxide with calcium aluminum hydroxide of a single-layer structure and calcines the mixture at a low temperature. Figure 3 As shown, nano-titanium dioxide can be attached to the single-layer structure of calcium aluminum hydroxide, achieving a better dispersion effect and avoiding the agglomeration and failure of nano-particles; further, through low-temperature calcination, the reaction activity of nano-titanium dioxide can be increased, so that the nano-titanium dioxide after low-temperature calcination can improve the durability and water stability of asphalt concrete.

[0030] In other embodiments, the first solid may be mixed with 1 to 5 parts by weight of nano titanium dioxide and then added into water, stirred for a second preset time, and filtered to obtain the second solid.

[0031] Preferably, after obtaining the third solid, the method further comprises: After the third solid is naturally cooled to room temperature, the third solid is mixed with 1 to 2 parts by weight of a phosphate coupling agent and crushed and ground to a powder fineness of a second preset size. The second preset size is: the fineness satisfies a pass rate of more than 90% on a 45µm square hole sieve.

[0032] Figure 1 and Figure 2 The XRD spectra of double-layer calcium aluminum hydroxide and single-layer calcium aluminum hydroxide are respectively. The present invention calcines kaolin in a high-temperature furnace at 700℃~900℃ for 3h~5h, which can remove hydroxyl groups and transform the regular crystal structure into an amorphous metakaolin structure, thereby improving the reaction activity of kaolin; the calcined kaolin and quicklime can undergo hydration reaction at room temperature to generate a large amount of double-layer calcium aluminum hydroxide and CSH gel; through further low-temperature calcination (i.e. calcination in a high-temperature furnace at 300℃~500℃ for 2h~4h), the double-layer structure of calcium aluminum hydroxide can be transformed into a single-layer structure, thereby achieving a significant increase in the specific surface area of ​​calcium aluminum hydroxide, and after being added to asphalt concrete, it can be filled in the asphalt concrete-aggregate interface to improve the anti-stripping performance; in the present invention, since CSH gel can also be used as an anti-stripping agent and the present invention does not require high purity of single-layer calcium aluminum hydroxide, there is no need to remove CSH gel before low-temperature calcination.

[0033] The following are several embodiments of the present invention. Except for Comparative Examples 3 and 4, the dosage of the anti-stripping durable modifier in the remaining embodiments and comparative examples is 0.5% of the weight of the asphalt concrete.

[0034] Example 1

[0035] The asphalt concrete anti-stripping durable modifier of this embodiment includes, by weight, 105 parts of calcium aluminum hydroxide with a single-layer structure, 1 part of nano titanium dioxide and 1 part of a phosphate coupling agent.

[0036] The chemical composition of kaolin, measured by mass fraction, includes 30% aluminum oxide and 50% silicon oxide. The fineness of kaolin is such that the passing rate of a 45µm square hole sieve is greater than 99%.

[0037] The preparation method of the anti-stripping durable modifier of this embodiment comprises the following steps: 90 parts by weight of kaolin is placed in a high-temperature furnace at 900° C. and calcined for 3 hours, and then placed in a 20° C. environment for 0 to 3 seconds for rapid cooling to obtain a first solid; The first solid was mixed with 65 parts by weight of quicklime and nano titanium dioxide, added into 90 parts by weight of water, stirred for 7 hours, and then filtered to obtain a second solid; The second solid is placed in a high-temperature furnace at 300°C and calcined for 4 hours. After naturally cooling to room temperature, it is mixed with a phosphate coupling agent and then crushed and ground to a powder fineness that satisfies a 45µm square hole sieve with a pass rate greater than 90%, thereby obtaining the asphalt concrete anti-stripping durable modifier prepared in this embodiment.

[0038] After the anti-stripping durable modifier is added in this embodiment, the performance test results of the asphalt concrete are shown in Table 1.

[0039] Example 2

[0040] The asphalt concrete anti-stripping durable modifier of this embodiment includes 90 parts by weight of calcium aluminum hydroxide with a single-layer structure.

[0041] The preparation method of the anti-stripping durable modifier of this embodiment comprises the following steps: 80 parts by weight of kaolin are placed in a high-temperature furnace at 700°C and calcined for 5 hours, and then rapidly cooled in a 40°C environment between 0 seconds and 3 seconds to obtain a first solid; the kaolin has a chemical composition of 30% aluminum oxide and 50% silicon oxide by mass, and the fineness of the kaolin satisfies a pass rate of more than 99% on a 45µm square hole sieve.

[0042] The first solid was mixed with 75 parts by weight of quicklime and nano titanium dioxide, added into 100 parts by weight of water, stirred for 5 hours, and then filtered to obtain a second solid; The second solid was calcined in a high-temperature furnace at 500°C for 2 hours, naturally cooled to room temperature, mixed with a phosphate coupling agent, and then crushed and ground to a powder fineness that met a 45µm square hole sieve pass rate of more than 90%, thereby obtaining the prepared asphalt concrete anti-stripping durable modifier.

[0043] After the anti-stripping durable modifier is added in this embodiment, the performance test results of the asphalt concrete are shown in Table 1.

[0044] Example 3

[0045] The asphalt concrete anti-stripping durable modifier of this embodiment includes 95 parts by weight of calcium aluminum hydroxide with a single-layer structure.

[0046] The preparation method of the anti-stripping durable modifier comprises the following steps: 85 parts of kaolin by weight are placed in a high-temperature furnace at 800°C and calcined for 4 hours, and then rapidly cooled in a 30°C environment within 0 to 3 seconds to obtain a first solid; the kaolin has a chemical composition of 30% aluminum oxide and 50% silicon oxide by mass fraction, and the fineness of the kaolin satisfies a pass rate of more than 99% on a 45µm square hole sieve.

[0047] The first solid is mixed with 70 parts by weight of quicklime and nano titanium dioxide, added into 95 parts by weight of water, stirred for 6 hours, and then filtered to obtain a second solid; The second solid was calcined in a high-temperature furnace at 400°C for 3 hours, naturally cooled to room temperature, mixed with a phosphate coupling agent, and then crushed and ground to a powder fineness that met a 45µm square hole sieve pass rate of more than 90%, thereby obtaining the prepared asphalt concrete anti-stripping durable modifier.

[0048] After the anti-stripping durable modifier is added in this embodiment, the performance test results of the asphalt concrete are shown in Table 1.

[0049] Comparative Example 1 The difference from Example 1 is that the asphalt concrete anti-stripping durable modifier is prepared from 105 parts of double-layer calcium aluminum hydroxide, 1 part of nano titanium dioxide and 1 part of phosphate coupling agent.

[0050] The preparation method of this comparative example is: 90 parts by weight of kaolin are placed in a high-temperature furnace at 900°C and calcined for 3 hours, and then rapidly cooled in a 20°C environment between 0 seconds and 3 seconds; the chemical composition of the kaolin, calculated by mass fraction, includes 30% aluminum oxide and 50% silicon oxide, and the fineness of the kaolin satisfies a pass rate of greater than 99% on a 45µm square hole sieve.

[0051] The calcined kaolin is mixed with 65 parts by weight of quicklime and nano titanium dioxide, added into 90 parts by weight of water, stirred for 7 hours, and then filtered to obtain a second solid; After the second solid is naturally cooled to room temperature, it is mixed with a phosphate coupling agent and then crushed and ground to a powder fineness that satisfies a 45µm square hole sieve pass rate of more than 90%, thereby obtaining the asphalt concrete anti-stripping durable modifier prepared in this comparative example.

[0052] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0053] Comparative Example 2 The difference from Example 1 is that the asphalt concrete anti-stripping durable modifier includes 105 parts of CSH gel, 1 part of nano titanium dioxide and 1 part of phosphate coupling agent.

[0054] The preparation method of this comparative example is: After mixing the CSH gel with nano-titanium dioxide, the mixture was added into 90 parts by weight of water and stirred for 7 hours, and then filtered to obtain a fourth solid. The preparation method of the CSH gel is a prior art and will not be described in detail. After the fourth solid is naturally cooled to room temperature, it is mixed with a phosphate coupling agent and then crushed and ground to a powder fineness that satisfies a 45µm square hole sieve pass rate of more than 90%, thereby obtaining the asphalt concrete anti-stripping durable modifier prepared in this comparative example.

[0055] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0056] Comparative Example 3 The difference from Example 1 is that the anti-stripping durable modifier is 2% of the weight of the asphalt concrete.

[0057] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0058] Comparative Example 4 The difference from Example 1 is that the anti-stripping durable modifier is 1% of the weight of the asphalt concrete.

[0059] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0060] Comparative Example 5 The difference from Example 1 is that the amount of nano titanium dioxide is 3 parts by weight.

[0061] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0062] Comparative Example 6 The difference from Example 1 is that the amount of nano titanium dioxide is 5 parts by weight.

[0063] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0064] Comparative Example 7 The difference from Example 1 is that the phosphate coupling agent is 1.5 parts by weight.

[0065] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0066] Comparative Example 8 The difference from Example 1 is that the phosphate coupling agent is 2 parts by weight.

[0067] After the anti-stripping durable modifier was added to the asphalt concrete in this comparative example, the performance test results are shown in Table 1.

[0068] Table 1 Test results of asphalt concrete anti-stripping performance

[0069] In Table 1, viscosity is used to evaluate the adhesion of asphalt concrete (i.e., anti-stripping), penetration is used to evaluate the durability of asphalt concrete, softening point is used to evaluate the high temperature resistance of asphalt concrete, and UV test is used to evaluate the anti-aging ability of asphalt concrete; the following conclusions can be drawn based on Table 1: It can be seen from Examples 1, 2, and 3 that as the amount of calcium aluminum hydroxide added to the single-layer structure increases, the adhesion (i.e., anti-stripping), anti-aging ability, high and low temperature stability, durability, and high temperature resistance of the asphalt concrete are enhanced, and the ductility loss rate is reduced; It can be seen from Example 1 and Comparative Example 1 that, compared with the anti-stripping durable modifier prepared from calcium aluminum hydroxide with a double-layer structure, the anti-stripping durable modifier containing calcium aluminum hydroxide of the present invention with a single-layer structure has significantly improved the strength, adhesion (i.e., anti-stripping), anti-aging ability, high and low temperature stability, durability and ductility loss rate of asphalt concrete; It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the high and low temperature stability, anti-stripping performance and durability of the asphalt concrete of the present invention are the best, and the ductility loss rate is the smallest; Figure 3 As shown, this is because the present invention, through low-temperature calcination, on the one hand, makes the nano-titanium dioxide dispersed and attached to the calcium aluminum hydroxide with a single-layer structure, thereby avoiding agglomeration, and on the other hand, increases the reactivity of the nano-titanium dioxide. However, the nano-titanium dioxide has poor dispersibility in the calcium aluminum hydroxide with a double-layer structure in Comparative Example 1 and the CSH gel in Comparative Example 2, respectively, which leads to poor anti-stripping and durability of the asphalt concrete. It can be seen from Example 1 and Comparative Examples 3 and 4 that as the amount of the anti-stripping durability modifier of the present invention increases, the anti-stripping performance and durability of the asphalt concrete are significantly improved. However, considering the preparation cost, the most appropriate amount is 1%. It can be seen from Comparative Examples 5 and 6 that with the increase in the amount of nano-titanium dioxide added, the durability of asphalt concrete is significantly improved; It can be seen from Comparative Examples 7 and 8 that with the increase in the dosage of phosphate coupling agent, the anti-stripping performance and durability of asphalt concrete are significantly improved. This is because the polar groups of the phosphate coupling agent can be adsorbed on the surface of the monolayer structure of calcium aluminum hydroxide and aggregate (such as acidic stone), respectively; the non-polar groups can combine with the asphalt concrete, thereby tightly combining the aggregate and asphalt concrete.

[0070] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a single-layer calcium aluminum hydroxide with a large specific surface area as an anti-stripping agent. After being added to asphalt concrete, it has a larger effective area with the asphalt concrete and the aggregate interface, so the asphalt concrete added with the present invention has better anti-stripping performance; (2) The asphalt concrete anti-stripping and durable modifier of the present invention uses kaolin and quicklime as main raw materials and is calcined in sequence at different temperatures, thereby converting the double-layer structure of calcium aluminum hydroxide into a single-layer structure, achieving a significant increase in the specific surface area of ​​calcium aluminum hydroxide. The preparation method is not only simple to operate and easy to control, but also effectively improves the performance of the modifier, providing asphalt concrete with excellent anti-stripping and durability performance; (3) The single-layer calcium aluminum hydroxide used in the present invention can reduce direct exposure to ultraviolet rays by physically shielding them, thereby reducing their damage and aging effects on asphalt concrete; (4) Furthermore, the single-layer calcium aluminum hydroxide used in the present invention can change the physical properties of asphalt concrete, such as viscoelasticity, creep deformation and elastic deformation, and improve the fatigue resistance of asphalt concrete. It can also improve the high-temperature stability, making it less likely to flow and deform under high temperature conditions, and improve the low-temperature crack resistance, preventing the asphalt concrete from cracking and damage under low temperature conditions. (5) The present invention can significantly improve the elastic modulus, yield stress and rheological properties of asphalt concrete and enhance its anti-deformation ability by adding nano-titanium dioxide with extremely small particle size and large specific surface area as powder filler. In addition, the nano-titanium dioxide of the present invention can also improve the adhesion between asphalt concrete and aggregate, reduce water damage, and enhance the anti-water damage performance of asphalt concrete. (6) The nano titanium dioxide of the present invention can improve the anti-aging performance of asphalt concrete, reduce the ductility loss rate of asphalt concrete under ultraviolet irradiation, reflect solar ultraviolet rays and increase heat dissipation, thereby reducing the surface temperature of asphalt concrete and improving the high-temperature stability of asphalt concrete; (7) The present invention contains micron-sized single-layer calcium aluminum hydroxide crystals, nano-sized titanium dioxide and phosphate coupling agent modifier, which can simultaneously improve the anti-stripping performance and durability (water stability, high temperature stability, low temperature stability, anti-ultraviolet aging performance, etc.) of asphalt concrete; (8) The present invention mixes nano-titanium dioxide with a single-layer calcium aluminum hydroxide and calcines at low temperature, so that the nano-titanium dioxide can be attached to the single-layer calcium aluminum hydroxide, achieving a better dispersion effect and avoiding the agglomeration and failure of the nanoparticles; further, the reaction activity of the nano-titanium dioxide can be increased by calcining at low temperature, so that the nano-titanium dioxide calcined at low temperature has an improvement effect on the durability and water stability of asphalt concrete; (9) The present invention adds a phosphate coupling agent. On the one hand, its multiple polar groups can be adsorbed on the surface of the single-layer calcium aluminum hydroxide and aggregate (such as acidic stone) respectively, so as to achieve uniform dispersion of the single-layer calcium aluminum hydroxide and avoid its agglomeration problem; on the other hand, its non-polar groups can combine with asphalt concrete, thereby closely combining the aggregate and asphalt concrete. This mechanism of action can significantly improve the anti-stripping performance of the asphalt concrete mixture and reduce the erosion of water on the asphalt concrete structure.

[0071] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An asphalt concrete anti-stripping durable modifier, characterized in that: The anti-stripping durable modifier comprises 90 to 105 parts by weight of calcium aluminum hydroxide with a single-layer structure.

2. The asphalt concrete anti-stripping durable modifier according to claim 1, characterized in that: The anti-stripping durable modifier also includes 1 to 5 parts of nano titanium dioxide by weight.

3. The asphalt concrete anti-stripping durable modifier according to claim 1 or 2, characterized in that: The anti-stripping durable modifier also includes 1 to 2 parts of a phosphate coupling agent by weight.

4. A method for preparing an asphalt concrete anti-stripping durable modifier, characterized in that: The following steps are involved: calcining 80 to 90 parts by weight of kaolin of a first preset size at a first preset temperature for a first preset time, and then rapidly cooling at a second preset temperature to obtain a first solid; Adding the first solid and quicklime into water, stirring for a second preset time, and filtering to obtain a second solid, wherein the quicklime is 65 to 75 parts by weight, the water is 90 to 100 parts by weight, and the second solid comprises a double-layer structure of calcium aluminum hydroxide; The second solid is calcined at a third preset temperature for a third preset time to obtain a third solid, wherein the third solid comprises: 90 to 105 parts by weight of calcium aluminum hydroxide with a single-layer structure.

5. The method for preparing the asphalt concrete anti-stripping durable modifier according to claim 4, characterized in that: After adding the first solid and quicklime into water, the method further comprises: 1 to 5 parts by weight of nano titanium dioxide are added to a mixture of the first solid, quicklime and water.

6. The method for preparing the asphalt concrete anti-stripping durable modifier according to claim 5, characterized in that: After obtaining the third solid, the method further comprises: After the third solid is naturally cooled to room temperature, the third solid is mixed with 1 to 2 parts by weight of a phosphate coupling agent and crushed and ground to a powder fineness of a second preset size.

7. The method for preparing the asphalt concrete anti-stripping durable modifier according to claim 4, characterized in that: The first preset temperature is 700°C to 900°C; the second preset temperature is 20°C to 40°C; and the third preset temperature is 300°C to 500°C.

8. The method for preparing the asphalt concrete anti-stripping durable modifier according to claim 4, characterized in that: The first preset time is 3h~5h; the second preset time is 5h~7h; and the third preset time is 2h~4h.

9. The method for preparing the asphalt concrete anti-stripping durable modifier according to claim 6, characterized in that: The first preset size is: the fineness satisfies that the pass rate of the 45µm square hole sieve is greater than 99%; the second preset size is: the fineness satisfies that the pass rate of the 45µm square hole sieve is greater than 90%.

Citation Information

Patent Citations

  • Environment-friendly elastomer modified asphalt waterproof material and preparation method thereof

    CN104312170A

  • Pervious concrete prepared from recycled aggregate and preparation process of pervious concrete

    CN110482936A

  • Synthetic method of calcium-aluminum hydroxide

    JP1996091831A

  • Production of calcium-aluminum-based layered double hydroxide

    JP2000264626A